Laying Hens Growth Performance in the Peak Production Phase Offered Bio-Herbal as a Feed Additive - Nuningtyas, Yuli Frita; Natsir, Muhammad Halim; Widyastuti, Eny Sri; Sjofjan, Osfar; Susilo, Agus; Widiati, Aris Sri; Lestari, Suci Puji (Jurnal Ilmu-Ilmu Peternakan, 2023)
The aim of this research was to evaluate the effect of the addition of bio-herbal as a feed additive on feed consumption, hen day production, feed egg ratio and mortality of laying hens. The materials in this experiment used 200 laying hens of the Hyline strain age 28 to 36 weeks (reared for 60 days). The method used in this study was an in vivo experimental method using a Completely Randomized Design (CRD) with treatments consisting of P0 = drinking water without bio-herbals (control treatment), T1 = control treatment + bio-herbal yellow, P2 = control treatment + bio-herbal green, and T3 = control treatment + bio-herbal combination yellow and green (alternately every one week). Data were analyzed using Analysis of Variance (ANOVA) and if there was a significant effect, then tested with Duncan's Multiple Range Test. The observed variables were feed consumption, Hen Day Production (HDP), feed egg ratio and mortality. The results showed that the addition of bio-herbals had no significant effect (P > 0.05) on the feed consumption, hen day production, feed egg ratio and mortality. It can be concluded bio-herbal green gives the best results in improving egg quality. Due to the bioactive compounds of bio-herbal green, they consist of probiotic and phytobiotic.